Kudüs’te Ebu Medyen El-Ğavs ve Şeyh Ömer El-Mücerred Vakıflarının Mali Durumu, 1855-1900 - Eroğlu Memiş, Şerife (FSM Vakıf Üniversitesi, 2020)
Ebu Medyen el-Ğavs’ın torunu Şuayb bin Muhammed bin el-Şuayb ve Şeyh Ömer el-Mücerred tarafından Meğaribe Mahallesi’nde kurulan vakıflar, Kudüs’te mukîm Mağribli Müslümanlar ile Mağribden gelen misâfir ve mücâvirlerin yeme-içme ve konaklama gibi çeşitli ihtiyaçlarını karşılamak üzere birer zâviye ihtiva etmekte idi. Gelirlerinin bir kısmını kırsal kaynaklardan elde eden bu vakıflar kentsel bazı gelirlere de sahipti. Hayrî ve mülhak bir yapıya sahip bu vakıflar şehir ekonomisi ile karşılıklı bir etkileşim halinde idi.Çalışma, vakıfların muhasebe defterlerini analiz ederek, kurumun 19. yüzyılın ikinci yarısındaki mali durumunu incelemektedir. Tarımsal ve kentsel gelirlerinde zaman zaman artışlar olan Ebu Medyen el-Ğavs ve Şeyh Ömer el-Mücerred Vakıfları,ilgili dönemde fiili işleyişini kesintiye uğratan bir mali bunalım döneminden geçmemiştir. Vakıfların mali durumu, kentsel koşulların vakıfları mali çöküntüye götürecek bir kötüleşme yaşamadığını da göstermiştir.

The waqfs, established by Abu Madyan Shuayb al-Maghribi,the grandson of Abu Madyan al-Ghawth, and Sheikh ‘Umar al-Mujarrad, in the Maghariba neighborhood in Jerusalem, included one lodge each to meet the various needs of Maghribi Muslims residing in Jerusalem, as well as guests and adjacents from the Maghrib, such as eating, drinking and accommodation. These waqfs, which collected a part of their income from rural sources, also had some urban incomes. Those, which were among charitable endowments and managed by the persons stipulated in their waqfiyyas were in mutual interaction with the economic conditions in the city.This study is to analyze the financial situation of the institutions in the second half of the 19th century by analyzing the waqfs’ accounting books. It reveals that while the agricultural and urban income of the waqfs increased from time to time, this did not bring about a period of financial crisis that interrupted their actual functioning. The financial situation of the waqf salso shows that the urban conditions did not deteriorate, which would lead to a financial collapse for both.
Financial Situation of the Waqfs of Abu Madyan Al-Ghawth and Sheikh ‘Umar Al-Mujarrad in Jerusalem, 1855-1900
Keywords: Ebu Medyen; Meğaribe; Vakıf; Kudüs; Muhasebe; Abu Madyan; Maghariba; Waqf; Jerusalem; Accounting